The potential of muscarinic M1 and M4 receptor activators for the treatment of cognitive impairment associated with schizophrenia - Yohn, Samantha E.; Harvey, Phillip D.; Brannan, Stephen K.; Horan, William P. (Frontiers in Psychiatry, 2024)
Cognitive impairment is a core symptom of schizophrenia and a major determinant of poor long-term functional outcomes. Despite considerable efforts, we do not yet have any approved pharmacological treatments for cognitive impairment associated with schizophrenia (CIAS). A combination of advances in pre-clinical research and recent clinical trial findings have led to a resurgence of interest in the cognition-enhancing potential of novel muscarinic acetylcholine receptor (mAChR) agonists in schizophrenia. This article provides an overview of the scientific rationale for targeting M1 and M4 mAChRs. We describe the evolution of neuroscience research on these receptors since early drug discovery efforts focused on the mAChR agonist xanomeline. This work has revealed that M1 and M4 mAChRs are highly expressed in brain regions that are implicated in cognition. The functional significance of M1 and M4 mAChRs has been extensively characterized in animal models via use of selective receptor subtype compounds through neuronal and non-neuronal mechanisms. Recent clinical trials of a dual M1/M4 mAChR agonist show promising, replicable evidence of potential pro-cognitive effects in schizophrenia, with several other mAChR agonists in clinical development.